Biochemistry - Berg, Jeremy M (W.H. Freeman, 2002)
With new co-authors Jeremy Berg and John Tymoczko, "Biochemistry" 5th edition has expanded integration of evolution, more chemical and structural insights, and a web based media component created simultaneously with the text.